2003
DOI: 10.1093/ajcn/77.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental tobacco smoke on vitamin C status in children

Abstract: ETS can reduce concentrations of ascorbate, an important blood antioxidant, even when the amount of smoke exposure is minimal. Children exposed to ETS should be encouraged to consume increased amounts of foods rich in vitamin C or should be given the equivalent amount of this vitamin as a supplement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
4
27
0
1
Order By: Relevance
“…Mandez et al (2002) exclusively studied ascorbic acid status in smokers and non-smokers and came to conclusion that smokers are at greater risk of chronic diseases due to low intake of ascorbic acid [10]. The observations of Preston et al (2003) are still more important in this regard who reported that ascorbic acid status is compromised in smokers and that environmental tobacco smoke reduces ascorbic acid status even when exposure to it is minimal [11].…”
Section: Discussionmentioning
confidence: 99%
“…Mandez et al (2002) exclusively studied ascorbic acid status in smokers and non-smokers and came to conclusion that smokers are at greater risk of chronic diseases due to low intake of ascorbic acid [10]. The observations of Preston et al (2003) are still more important in this regard who reported that ascorbic acid status is compromised in smokers and that environmental tobacco smoke reduces ascorbic acid status even when exposure to it is minimal [11].…”
Section: Discussionmentioning
confidence: 99%
“…201 Another risk group is children exposed to environmental tobacco smoke via passive smoking. Even at a low amount of smoke exposure, children showed reduced plasma ascorbate concentrations, by an average of 3.2 µmol/l compared with unexposed children who received equivalent quantities of vitamin C. 176 Plasma ascorbic acid concentrations in passive smokers were intermediate between levels found in smokers and those found in non-exposed non-smokers. 242 Hypovitaminosis C (i.e.…”
Section: Deficiencies: Relevance and Prevalencementioning
confidence: 90%
“…123 After controlling for age, gender, vitamin C intake, and multivitamin use, children exposed to high levels of SHS had about the same reduction in serum ascorbic acid levels observed in children who were active smokers ( Table 2). Preston et al 124 found plasma vitamin C levels to be on average 3.2 mol/L lower in children exposed to SHS compared with unexposed children (both groups had similar dietary intake of vitamin C).…”
Section: Decreased Antioxidant Levelsmentioning
confidence: 99%